(untitled) (Международный научный журнал «Инженер», 2026)
This article considers the application of the finite element method in modeling bridge supports, taking into account various types of loads - static, dynamic and temperature effects. To achieve this goal, the Lira-CAD software package was selected, which allows analyzing structures with a full reflection of their geometry, along with their physical and mechanical properties. This system provides extensive opportunities for accurately determining load parameters, taking into account seismic and other external influences. The finite element approach simplifies the calculation process by dividing structures with complex geometry into simpler elements, which increases the accuracy of engineering analysis and plays an important role in ensuring the reliability and service life of structures.